A Survey of Technologies for Building Collaborative Virtual Environments - Wright, Timothy E.; Madey, Greg (International Journal of Virtual Reality, 2009)
What viable technologies exist to enable the development of so-called desktop virtual reality (desktop-VR) applications? Specifically, which of these are active and capable of helping us to engineer a collaborative, virtual environment (CVE)? A review of the literature and numerous project websites indicates an array of both overlapping and disparate approaches to this problem. In this paper, we review and perform a risk assessment of 16 prominent desktop-VR technologies (some building-blocks, some entire platforms) in an effort to determine the most efficacious tool or tools for constructing a CVE